Novel Approaches for the Delivery of Anti-HIV Drugs - das Neves, José (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
HIV/AIDS continues to be one of the most challenging individual and public health concerns of the present day. According to the UNAIDS, nearly 38 million individuals were living with the infection by the end of 2018, while 1.7 million new cases occurred during that same year. In spite of the numerous advances in the development and delivery of antiretroviral agents, both for treatment and prevention, several challenges remain. This book includes original research and review articles on innovative strategies and approaches for the formulation and delivery of anti-HIV drugs, including genetic material and other biopharmaceuticals. Different local and systemic delivery strategies are addressed based on different technologies intended for oral, transdermal, subcutaneous, vaginal, or rectal administration. Authored by eminent scientists in academia and nonprofit organizations involved in the development of antiretroviral drug products, this collection provides useful information for all those involved in HIV/AIDS treatment and prevention.